Literary Studies and Well-Being - Ronald Schleifer (Bloomsbury Academic, 2022)
The literary arts represent and provoke experiences of understanding and emotion, and this open access study examines how the practical pursuit of well-being in healthcare reveals purposes at the core of our engagements with and understanding of literature itself. During the past twenty years, much admirable work in the
10.5040/9781350335714
Keywords: Health humanities; Literature; Well-being